Afghanistan Diagnostics Trade Integration Study - World Bank (Washington, DC, 2013)
Trade enables countries to import ideas and technologies, realize comparative advantages and economies of scale, and foster competition and innovation, which in turn increases productivity and achieves higher sustainable employment and economic growth. Countries open to international trade tend to provide more opportunities to their people, and grow faster. Afghanistan could derive far more benefit from its international trade opportunities than it does at present. This Diagnostics Trade Integration Study (DTIS) report is intended to identify concrete policy actions in three areas of endeavor: lowering the transaction costs of trade, increasing Afghanistan's competitiveness in world markets, and providing an analytical foundation for Afghanistan's national trade strategy. The study examines how to do this, looking not only at trade performance and policy, but also at three sectors with great export potential: agriculture, gemstones and carpets, as well as the investment climate, customs as a driver of trade facilitation, and on promoting infrastructure services. All five chapters in this report provide a detailed and comprehensive analysis of trade issues intended to reduce the transaction costs of trade. Growth in Afghanistan has been strong and volatile because of its heavy reliance on agriculture. Now it faces a transition: prospects of a drawdown of international military forces and a decline in civilian aid by 2014. Security issues and political instability could undermine Afghanistan's Transition. Such threats could harm not only economic growth, but deterioration would repel private-sector investment.